A Case of Chronic Viral Hepatitis Caused by HEV Genotype 1F - Roy Biswas, Rajat Sanker; Sydu, Sydujjaman (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: An acute hepatitis caused by Hepatitis E Virus (HEV) is a significant global health concern, especially in developing countries like Bangladesh. HEV has 1 serotype and 8 genotypes, which are further divided into subtypes. Despite the availability of sporadic cases and outbreak data from Bangladesh no case was reported regarding its chronicity and identification of genotype in our context. So the objective of the case report is to provide a data of a HEV induced chronic hepatitis with its genotype result. Case Presentation: Present case is a 38 years male presented with features chronic hepatitis for more than four months. After clinical evaluation and different biochemical and serological tests he was diagnosed as a case of HEV induced chronic viral hepatitis. Genotype of the virus was also done from USA based research lab where HEV genotype 1F was found as the culprit. It is the commonest genotype found in the South East Asia region found in different epidemiological data. Conclusion: It is well known that HEV can cause acute and fulminant viral hepatitis but rarely it can also cause chronic hepatitis as in the present case. JCMCTA 2022 ; 33 (2) : 133-135